Encouraging the Use of Digital Payment Systems By QRIS Among Traditional Market Traders - Siti Maria; Anggi Oktawiranti; Justina Ade judiarni; Heni Rahayu Rahmawati; Hidayani Hidayani (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Digital transformation in the payment system is one of the important factors in improving transaction efficiency in traditional markets. Quick Response Code Indonesian Standard (QRIS) has been introduced as a digital payment solution that can be applied in various sectors, including traditional markets. However, the adoption of QRIS by market traders still faces various challenges, such as low digital literacy, limited devices, and resistance to changes in the transaction system. This study aims to analyze the level of understanding and readiness of Segiri Market traders in adopting QRIS, as well as evaluate the effectiveness of training and mentoring in increasing the adoption of this digital payment system. The methods used in this study include socialization, training, and simulation of QRIS transactions to market traders. The pre-test and post-test results showed a significant increase in merchants' understanding and readiness to use QRIS, with the willingness to adopt increasing from 40% to 90%. In addition, increased convenience in digital transactions and frequency of QRIS usage also showed a positive trend after the intervention. The conclusion of this study is that continuous education and mentoring is essential in driving QRIS adoption in traditional markets. Collaboration between the government, banks, and financial service providers is needed to ensure the sustainability of digital payment implementation in the traditional trade sector.